Madonna or Don McLean? The effect of order of exposure on relative liking - Pandelaere, Mario; Millet, Kobe; Van den Bergh, Bram (Journal of Consumer Psychology, 2010)
Abstract While many studies have shown that exposure frequency affects consumer attitudes and preferences, the current paper provides evidence that exposure order also does so. Three studies show that people like stimuli to which they are first exposed better than later encountered, similar stimuli. Controlling for exposure frequency and duration, individuals prefer the version of a song they heard first to a version they heard later and images they saw first to mirror images they saw later. In addition, our results suggest that perceived originality contributes to the preference for a first encountered stimulus. Our results are discussed in relation to research on order effects in sequential rating formats.